Teaching literature in ESL in a Malaysian context: (proposed INSET course designs for literature in ESL instruction) - Talif, Rosli (1991)
In view of the recent introduction of a literature component in the Malaysian English language teaching syllabus, this research study sets out to determine the present situation concerning the teaching of literature in ESL in Malaysia with particular reference to the Class Reader Programme (CRP). This is in order to develop two proposed course designs for the teaching of literature in ESL at the secondary school level with special emphasis on the Malaysian context. Under the present circumstances, this study offers an immediate response to the new developments and challenges brought about by the literature in ESL programmes especially when the Malaysian Education Ministry implemented the CRP at the Form One level in all secondary schools beginning from the 1989 academic year. The Ministry also plans to introduce the forthcoming Elective Literature in English Programme (ELEP) for the upper secondary level (Forms Four-Five) during the 1991-92 school session. These programmes aim to introduce the use of literary texts for language and literary purposes. This study is also in line with the current effort undertaken by the Department of Languages at the Universiti Pertanian Malaysia (UPM) to develop teaching literature in ESL courses for its pre- and in-service education and training (INSET) programme. Questionnaires were developed and used as the means for gathering the data in three separate surveys which were carried out for the purposes of this study. The three respective surveys were to investigate: (1) the Universiti Pertanian Malaysia (UPM) TESL in-service teachers' training to teach literature in ESL in Malaysia; (2) teachers' response to the CRP; and (3) teachers' response to the needs analysis of course components for teaching literature in ESL in Malaysia. In addition, separate interviews which involved two assistant directors from the Ministry of Education, Malaysia had also been undertaken to obtain further information pertaining to the aims and implementation procedures for the literature in ESL programmes (CRP and ELEP) at the secondary school level in Malaysia. The sample for this study consisted of 144 in-service teachers at UPM who were undergoing a four-year Bachelor of Education (B. Ed.) programme in Teaching English as a Second Language (TESL) and twenty-three Form One English language teachers from eleven selected rural and urban secondary schools in Malaysia who had been involved with the CRP. The outcome of this study primarily revealed that in the English language syllabus the respondents were not adequately prepared to teach the literature component; thereby, establishing the need for teaching literature in ESL courses in teacher education programmes in Malaysia. In relation to this finding, two proposed course designs which cater for the integrated language and literature teaching programmes in Malaysia (CRP and ELEP) were developed as an initial and practical response toward this undertaking. The two proposed courses are known as "Literature in ESL in the Language Class" and "Literature in ESL in the Literature Class”. Essentially, these two complementary courses promote the use of literary texts in the ESL classroom. Due consideration had been given to the following factors in the process of developing the two proposed courses: (1) the aims and objectives of the literature in ESL programmes in Malaysia (CRP and ELEP); (2) the results of the three empirical surveys which were conducted for the purposes of this study; (3) the review of the literature; and (4) the researcher's five years of practical experience in working with the Teaching of English as a Second Language (TESL) pre- and in-service teacher training and development programme at UPM. It is hoped that the results of this study will have some implications for future considerations on teaching literature in ESL courses, particularly in Malaysia, and also provide some basic principles and directions for future research in the area. More importantly, this initial effort should be regarded as a primary attempt to address the inadequacy of courses on methodology in the teaching of literature in ESL in the Malaysian teacher education curriculum. It may also serve as a practical guide to those who are interested in understanding more about the nature of literature teaching in ESL in general and in the Malaysian context in particular.